Aroma formation in Dianhong black tea: Effects of baking. Issue 11 (2nd November 2017) - Qiu, Xueli; Wang, Jianxin; Yu, Xiaofen; Lv, Shidong; Wu, Yuanshuang; Wang, Chen; Gao, Xuemei; Li, Jiangbing; Zhang, Wenrui; Zhao, Peng; Meng, Qingxiong
ABSTRACT: Baking is the last, and yet most essential, step in the formation of the final distinct flavour of most black tea products. In this study, the influence of baking on the volatile components of Dianhong black tea, which is one of the most popular black teas in China, was investigated. As a very fast, effective, and simple method for collecting volatiles, headspace solid-phase microextraction (HS-SPME) with a 65 µm PDMS/DVB fibre was used to extract the volatile compounds of Dianhong black tea, and the volatile components were further separated and identified by gas chromatography-mass spectrometry (GC-MS). The results showed that the peak areas of alcohols, aldehydes, esters, and ketones were increased, but that those of some alkanes, acids, and nitrogen compounds did not demonstrate an obvious increase after baking. The differences generated by baking process actually result in the distinct flavour of most black teas and can be used as a model for analysing the chemical composition of special flavours, and for quality improvement and process control.